Kontektualisasi Injil Dalam Budaya Populer untuk Menjangkau Masyarakat Urban - Degunias Ton (Kharisma: Jurnal Ilmiah Teologi, 2023)
AbstractThe existence of traditional culture is increasingly being displaced by the rise of popular culture which is loved by urban communities. Then the next question arises, how to contextualize the Bible in this popular culture to reach urban communities. The method used in this study is a descriptive qualitative approach by conducting a literature study. The purpose of this research is to find out the contextualization that can be done as a form of preaching the Gospel through popular culture. The forms of popular culture raised are social media, traveling and culinary tourism. For the sake of spreading the Gospel, it is necessary to have a deep understanding and application of the preaching of the Gospel that is relevant to the growing popular culture. Furthermore, this article proposes a contextualization dialectic model as a concept of contextualizing the Bible in which there are stages of adaptation to context, enculturation, semiotics and gospel practice to reach urban communities. By using the dialectic model of contextualization in popular culture, the Bible is more relevant to urban society.AbstrakKeberadaan budaya tradisional semakin hari semakin tergeser dengan maraknya budaya populer yang digandrungi oleh masyarakat urban. Maka selanjutnya muncul pertanyaan, bagaimana mengkontekstualisasikan Injil di dalam budaya populer ini untuk menjangkau masyarakat urban. Metode yang digunakan dalam kajian ini adalah pendekatan kualitatif deskriptif dengan melakukan studi pustaka. Tujuan penelitan ini untuk mengetahui kontektualisasi yang dapat dilakukan sebagai bentuk pemberitaan Injil melalui budaya populer. Adapun bentuk-bentuk budaya populer yang diangkat adalah yaitu bermedia sosial, traveling dan wisata kuliner. Untuk kepentingan penyebaran Injil maka diperlukan pemaknaan mendalam dan pengaplikasian pemberitaan Injil yang relevan dengan budaya populer yang berkembang. Selanjutnya, artikel ini mengajukan model dialektika kontekstualisasi sebagai konsep kontekstualisasi Injil yang didalamnya terdapat tahap adaptasi dengan konteks, tahap enkulturasi, tahap semiotik dan tahap praktik injil untuk menjangkau masyarakat urban. Dengan menggunakan model dialektika kontekstualisasi dalam budaya populer, Injil lebih relevan diterima oleh masyarakat urban.